Nursing Diagnosis in Home Care: Audit Tool Development - Zink, M.R. (Journal of Community Health Nursing, 1994)
Little research has been done to document the value of using nursing diagnosis in home care and the impact that increased acuity levels have had in diagnostic selection. Nursing diagnosis documentation in home care was examined to see whether it had a relation to select client and visit pattern variables. This retrospective chart audit, which piloted a newly developed instrument called the Home Care Audit Tool, utilized a sample of 199 closed records of a large midwestem Visiting Nurse Association. The mean age of the client population was 76 years, with 64% female. There were 269 initial nursing diagnoses cited in the sample records, averaging 1.75 diagnoses per case. The number of recorded visits increased when select nursing diagnoses were cited together in a single case. © 1994, Taylor & Francis Group, LLC. All rights reserved.
Keywords: Aged; Community Health Nursing; Female; Home Care Services; Human; Male; Models, Nursing; Nursing Audit; Nursing Diagnosis; Nursing Records; Pilot Projects; Reproducibility of Results; Retrospective Studies; Severity of Illness Index; article; community care; dept.nur; home care; medical assessment; nursing; nursing education